Coupling excavator hydraulic system and internal combustion engine models for the real-time simulation. (August 2015) - Casoli, Paolo; Gambarotta, Agostino; Pompini, Nicola; Riccò, Luca
Abstract: Rising energy costs and emissions restrictions force manufacturers to exploit new techniques to reduce fuel consumption and pollutant production. Many solutions have been proposed for off-road vehicles, mainly based on reduction of hydraulic losses, better control strategies and introduction of hybrid architectures. In these applications the optimisation of the matching between hydraulic system and thermal engine is a major concern to improve system overall efficiency. The work presented in the paper is focused on the development of a method for the simulation of typical mobile machinery where hydraulic systems are powered by internal combustion engines; the proposed co-simulation approach can be useful in the development cycle of this machinery. Highlights: A co-simulation approach useful in the development cycle of hydraulic systems powered by thermal engines. Coupling models of a Diesel engine and of a hydraulic circuit. The complete model of the system can be used for the Real-Time simulation.